(untitled) (Journal of Universal Science Research, 2024)
This article presents an exploration of the Termiz Archaeological Museum, the sole museum of its kind in Central Asia. Situated in southern Uzbekistan, Termiz is renowned for its rich historical heritage, shaped by the influences of ancient civilizations and medieval empires that traversed the region along the Silk Road. The Termiz Archaeological Museum serves as a custodian of this heritage, showcasing artifacts and archaeological finds that offer insights into the region’s diverse cultural landscape. Through a journey into the museum’s collections and exhibitions, this article unveils the treasures of Central Asia’s cultural gem, shedding light on its historical significance and cultural identity.